Basal Cell Adenoma of the Upper Lip from Minor Salivary Gland Origin - Minicucci, Eliana Maria; Eloisa, Eloisa Bueno Pires de; Weber, Silke Anna Thereza; Domingues, Maria Aparecida Custodio; Ribeiro, Daniel Araki (European Journal of Dentistry, 2008)
Basal cell adenoma is an uncommon benign salivary gland neoplasm, presenting isomorphic basaloid cells witha prominent basal cell layer. Taking into account that basal cell adenomas represent 1% of all salivary gland tumors, being the majority of cases in the parotid glands, the goal of this paper is to report a case of basalcell adenoma of the upper lip arising from minor salivary gland. (Eur J Dent 2008;2:213-216)
Keywords: Basal cell adenoma; Minor salivary gland; Immunohistochemistry